1996
DOI: 10.1017/s0043174500094807
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max) Response to Weed Interference and Rhizoctonia Foliar Blight (Rhizoctonia solani)

Abstract: Field studies evaluated response of soybean to Rhizoctonia foliar blight (RFB) disease in combination with varying densities of common cocklebur, hemp sesbania, or johnsongrass. Soybean plants at both V10 and R1 growth stages were not inoculated or inoculated with suspensions containing equal concentrations ofRhizoctonia solaniAG-1 IA and IB mycelia. Intensity of RFB was rated weekly beginning at V1 soybean growth stage, and data were used to determine area under disease progress curves. Intensity of RFB was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Ear and ovule development in dent corn was delayed when late vegetative stages are subjected to drought stress (Ritchie et al 1993), an environmental condition that could be exacerbated by weed interference. Black et al (1996) reported delays in soybean maturity from hemp sesbania [Sesbania exaltata (Raf.) Rydb.]…”
Section: Resultsmentioning
confidence: 99%
“…Ear and ovule development in dent corn was delayed when late vegetative stages are subjected to drought stress (Ritchie et al 1993), an environmental condition that could be exacerbated by weed interference. Black et al (1996) reported delays in soybean maturity from hemp sesbania [Sesbania exaltata (Raf.) Rydb.]…”
Section: Resultsmentioning
confidence: 99%